Study on network structure characteristics of boxers' physical fitness system from the perspective of complex network - Zhang, H.; Fan, Q. (Advances in Social Science, Education and Humanities Research, 2020)
This paper analyses the complex relationship and structural characteristics of the indicators of male boxers' strength and conditioning system from the perspective of network science. The paper also explores the core indicators of the system under different dimensions. In it, a test index system was established according to the physical characteristics of boxing. Based on the test results, the network model of the physical system of male boxers was established and the network attributes were calculated. Results: 1) There are 156 correlations among the 43 indicators of the strength and conditioning system of men's boxing. The lowest correlation is 1, the highest is 15, and the average is 6.6383. 2) Any indicator in the physical network can affect another indicator through an average of 2.8032 edges. The clustering coefficient of the network is 0.6075, which indicates that the network connection is very close. 3) The maximum strength of weight and bench press are the core indicators of the strength and conditioning system of male boxers under the four central dimensions. 4) The network has obvious structural division with the module value of Q=0.45. The network consists of two large and four small sub-networks. The indicators of the strength and conditioning system of male boxers vary according to their attributes, thus having different impact on the whole system. These indicators do not function independently based on their different characteristics. Instead, they correlate with each other and have influence on each other as an integration. This will help find out method leading to higher level of physical performance of male boxing athletes.